EVALUATING THE USE OF THE COGNITIVE WALK- THROUGH USABILITY - PENHA, Alice Demaria Silva; SANTOS, Flávio Anthero Nunes Vianna dos (Human Factors in Design, 2012)
<!– /* Font Definitions */ @font-face font-family:Times; panose-1:2 0 5 0 0 0 0 0 0 0; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:3 0 0 0 1 0; @font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:3 0 0 0 1 0; @font-face font-family:"Minion Pro"; panose-1:2 4 5 3 5 2 1 2 2 3; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:3 0 0 0 1 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-ansi-language:PT-BR; p.MsoFootnoteText, li.MsoFootnoteText, div.MsoFootnoteText mso-style-noshow:yes; mso-style-link:"Footnote Text Char"; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-ansi-language:PT-BR; p.Corpo, li.Corpo, div.Corpo mso-style-name:Corpo; mso-style-parent:"Footnote Text"; margin:0cm; margin-bottom:.0001pt; text-indent:36.0pt; line-height:150%; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-ascii-font-family:"Minion Pro"; mso-fareast-font-family:Times; mso-hansi-font-family:"Minion Pro"; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-ansi-language:PT-BR; span.FootnoteTextChar mso-style-name:"Footnote Text Char"; mso-style-noshow:yes; mso-style-locked:yes; mso-style-link:"Footnote Text"; mso-ansi-font-size:12.0pt; mso-bidi-font-size:12.0pt; mso-ansi-language:PT-BR; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <p class="Corpo" style="margin-top: 0cm; margin-right: 0cm; margin-bottom: 14.4pt; margin-left: 21.3pt; mso-para-margin-top: 0cm; mso-para-margin-right: 0cm; mso-para-margin-bottom: 1.2gd; mso-para-margin-left: 21.3pt; text-indent: 0cm; line-height: normal; tab-stops: 21.3pt;"><span style="font-size: 11.0pt; font-family: Calibri; mso-ascii-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Calibri; mso-bidi-theme-font: minor-latin; mso-ansi-language: EN-US;">This paper addresses the evaluation of the Cognitive-Walk-Through (CWT) usability method by the application of an experiment with two groups: the control group and the experimental group. While one group carried out an assessment task without the use of a method, the other group used the CWT method. Both groups were intentionally assembled only with designers with the purpose to evaluate the ability of the proposed method: the possibility of the expert to place him or herself as the user. Although both groups came up with similar answers, meaningful differences were noticed. The evaluation of the group that used the method was deeper and more sensitive to the condition of the user. Furthermore, the method proved itself as an important guide in the search for answers focused on the demanded task.